Detection of Spatiotemporal Interferences of Road Traffic with IoT-Connected Sensor Beacons. Issue 4 (2021) - Czogalla, Olaf; Schönrock, René
Abstract: Efficient collection and real-time provision of information on roadworks with impact on traffic flow are essential to reliable and effective traffic and transport management for urban and regional road networks. In order to enable road operators to impose efficient traffic management measures, comprehensive amounts of data on both traffic demand and interferences of the road infrastructure are required. Roadworks management systems are used for planning of construction work zones, whereas exact real-time information on opening, spatial-timely progress and completion of roadworks are only to obtain by connected sensors to be deployed directly in the work zone. To that end, an innovative sensor-based construction barricade light - in the following denoted as sensor beacon - has been developed which allows the geo-referencing of road works in real time with sub-meter accuracy. The combined use of multiple connected sensor lights allows the extent of the work site to be exactly mapped. The construction site related information is provided to an urban data platform for further processing with software systems for roadworks information and coordination.